The Effect of Planting Media and Liquid Organic Fertilizer Interval on the Growth and Yield of Chili Peppers - Haryuni; Rani Latifah; Achmad Fatchul Aziez; Endang Suprapti; Tyas. S. K. Dewi; Siti Mardhika Sari (Agricultural Science, 2025)
This study aims to determine the effect of planting media and the interval of application of liquid organic fertilizer of banana stems on the growth and yield of chili pepper plants (Capsicum frutescens L.). The study was conducted in the greenhouse of the Faculty of Agriculture, UTP Surakarta from December 2024 to February 2025 using a factorial complete randomized block design (RAKL) with two factors: planting media (soil, soil + manure, soil + manure + rice husks) and the interval of application of liquid organic fertilizer (without liquid organic fertilizer, once every 5 days, once every 10 days, once every 15 days). The results showed that the planting media of soil + manure + rice husks (M2) had a very significant effect on plant height, fresh weight, dry weight, number of fruits, and harvested fruit weight, with the highest results in plant height (74.729 cm), fresh weight (76.688 g), and harvested fruit weight (576.75 g). The 15-day liquid organic fertilizer application interval (P3) also showed a significant effect on plant growth and yield, with the highest plant height (67.336 cm) and the highest harvest fruit weight (524.56 g). The conclusion of this study is that the use of a mixture of soil, manure, and rice husks as a planting medium and a 15-day POC application interval is the best combination to increase the growth and yield of chili pepper. This study also shows that banana stem liquid organic fertilizer can be an alternative environmentally friendly and sustainable organic fertilizer.